"Are We Really Not Going to Talk about the Black Girl?": The Intergroup Racial Attitudes of Senior, White, Sorority Women. Issue 2 (4th May 2018) - Zimmerman, Hilary B.; Morgan, Demetri L.; Terrell, Tanner
Abstract : Despite the positive effects of cross-racial interactions for students, predominantly White sororities remain segregated. Utilizing focus group methods, this study investigates the racial attitudes of White sorority women to understand the influence of sororities on racial attitudes. Findings revealed that participants in this study minimized race, thought about diversity within context, and perceived barriers to cross-racial interactions. These findings have important implications for campus professionals who work with sorority women.